Teacher selection: Evidence-based practices - Klassen, Robert M.; Kim, Lisa E. (Springer, 2021)
1. The importance of selecting the most effective teachers -- 2. Teacher effectiveness -- 3. Predicting teacher effectiveness -- Part II. Research on selection practices: A look at the evidence -- 4. Selection theory and research -- 5. Selection practices in other fields -- 6. Issues and problems in selection -- Part III. Teacher selection: past, present, and future -- 7. Teacher selection: history and current practices -- 8. New approaches to teacher selection -- 9. Implementation of teacher selection methods -- 10. The road ahead: the future of teacher selection practices.
Keywords: Auswahlverfahren; Lehrer; Educational psychology; Education—Psychology; Assessment; Industrial psychology; Teaching; Educational policy; Education and state